Psychedelics as novel therapeutic agents for chronic pain: mechanisms and future perspectives - Bushra Yasin; Shivani Mehta; George Tewfik; Alex Bekker (Exploration of Neuroscience, 2024)
Chronic neuropathic pain is a significant public health issue affecting an estimated 1.5 billion individuals worldwide. The mechanisms underlying chronic pain are multifaceted and not fully understood. Chronic pain amplifies specific neural pathways through peripheral and central sensitization triggered by repeated exposure to noxious stimuli, ultimately resulting in physical and emotional pain. Traditional treatment options targeting these mechanisms, such as opioid and non-opioid analgesics, are associated with adverse effects, addiction, and suboptimal pain relief. Using psychedelics to treat chronic pain is an area of growing interest. While psychedelic substances, such as psilocybin, lysergic acid diethylamide, mescaline, and 3,4-methylenedioxymethamphetamine are primarily associated with recreational use or spiritual practices, emerging evidence suggests their potential therapeutic benefits for various mental health disorders, including chronic pain. Psychedelics alter pain perception by directly activating serotonin receptors, exerting anti-inflammatory effects, enhancing descending inhibition, opening a window of neuroplasticity, and facilitating synaptic remodeling. This review mainly elucidates the ongoing research regarding the psychedelic mechanisms of action, pharmacology, clinical applications, and therapeutic potential in treating neuropathic pain.